Transformasi Digital dalam Bisnis Internasional: Tinjauan Literatur tentang Dampaknya terhadap Operasional dan Pemasaran Global - Siregar, Ewi Sarlina; Rahmat, Hayatul Khairul; Billah, Mhd. Adil Almu'tasim; Nurmita, Septia; Nurbit, Nurbit; Sispurwanto, Yedi; Kurniawan, Gilang; Aritonang, Kristian (Journal of Current Research in Management, Policy, and Social Studies, 2025)
Digital transformation in international business has significantly impacted how companies operate and interact with consumers, reshaping the competitive landscape in global markets. The integration of advanced technologies such as Artificial Intelligence (AI), Big Data analytics, the Internet of Things (IoT), and cloud computing has revolutionized internal processes, customer relationships, and market expansion strategies. This study explores the effects of digitalization on operational efficiency, marketing strategies, and customer experiences within multinational corporations. It highlights how digital transformation not only reduces costs and enhances decision-making but also enables companies to create sustainable competitive advantages in a rapidly changing global business environment. Despite the numerous benefits, companies face challenges related to implementation costs, skill gaps, and data security, which must be overcome to fully leverage the opportunities presented by digital technologies.